IMPLEMENTASI HOUSE OF RISK (HOR) PADA PETANI DALAM AGRIBISNIS MANGGA GEDONG GINCU - Pedekawati, Cindy; Karyani, Tuti; Sulistyowati, Lies (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2017)
Agribusiness gedong gincu mango can not be separated from the risk in various sources such as production risk, price / market risk, human risk, financial risk and institutional risk. All these sources of risk have the potential to cause disruption to the production process to the entire agribusiness process and ultimately affect the income of the gedong gincu mango farmers in Sedong District. Therefore, it is necessary to identify risk and resource occurrences (risk agents) that are frequent and likely to reappear and designing mitigation actions to minimize those risks. This research using House of Risk model (HOR) which consist of 2 phases. The first phase is the identification of risk and risk agents, which then measured the level of severity and occurance as well as calculating the value of Aggregate Risk Priority (ARP). The second phase of risk management. After the research, there were 20 risk events and 12 risk agents. There are 5 mitigation actions that can be used, in the hope of mitigating the risks on agribusiness gedong gincu in Sedong District.